Simulations of γ-Valerolactone Solvents and Electrolytes for Lithium Batteries Using Polarizable Molecular Dynamics - Adriano Pierini; Valentina Migliorati; Juan Luis Gómez-Urbano; Andrea Balducci; Sergio Brutti; Enrico Bodo (Molecules)
In this paper, we present a molecular dynamics study of the structural and dynamical properties of γ-valerolactone (GVL) both as a standalone solvent and in electrolyte formulations for electrochemistry applications. This study involves developing a new parameterization of a polarizable forcefield and applying it to simulate pure GVL and selected salt solutions. The forcefield was validated with experimental bulk data and quantum mechanical calculations, with excellent agreement obtained in both cases. Specifically, two 1M electrolyte solutions of lithium bis(fluorosulfonyl)imide and lithium bis(oxalate)borate in GVL were simulated, focusing on their ionic transport and highlighting ion solvation structure. Ion pairing in the electrolytes was also investigated through enhanced sampling molecular dynamics, obtaining a detailed picture of the ion dynamics in the GVL solution.